(untitled) (Mongolian Journal of Agricultural Sciences, 2021)
Soybean has a lot of benefits for human nutrition, well-being and soil nutrition. Soybean seed contain higher concentration of protein and fat. The objective of this work was to evaluate the nutritional composition and mineral contents in soybean seeds of four different varieties of soybean for their future application as food products. The soybeans were cultivated in Mongolia. The moisture, protein, crude fat, reducing carbohydrate’s concentrations were determined by Kjeldahl, Soxhlet and Bertrand’s method in dried soybean seeds, and the calory of 100 g seed was calculated. The mineral concentration in the ash was determined by ICP-OES method. Among them, the Severnaya-4 variety contained the highest amount of protein, 31.5%, the Sibiryachka variety had the highest concentration of crude fat, 20.35%, and reducing sugar, 1.24%. Moreover, the Severnaya-4 and Sibiryachka soybean seeds had the highest mineral concentration. The lower concentration of protein of these four soybean varieties was probably due to the lower temperature during the seed-filling period in Mongolia. Sibiryachka and OAC vision had the highest amount of energy in 100 g raw seed than other two varieties. The Severnaya-4 and Sibiryachka soybean seeds could be better sources for protein, fat and minerals than the Nei dou-4 and OAC vision varieties.